Investment Trends in the Iraqi Oil Sector (Upstream – Oil Refining – Gas Treatment - Transportation - Distribution) (2003 – 2020) - Fahad, Aysar Y.; Shaalan, Hisham Yas (Journal of Petroleum Research and Studies, 2022)
The paper deals with the analysis of indicators of changes in investment in the oil sector in Iraq to study the traditional patterns and the current patterns developed for oil investment in the extractive, transformational and distributive fields that were employed in Iraq to redraw the map of the economy in general and the oil industry in particular. The paper proceeds from the premise that the licensing rounds that took place in the Iraqi oil sector did not show their tangible results for internal and external reasons that were diagnosed. The study reached the main conclusion that the real performance and progress in the Iraqi oil sector was unbalanced and slow in some areas and that investment in it would create a balance between the urgent needs for expansion of investment projects and their capital requirements.